Effect of Crystallinity of Synthetic Graphite on Electrochemical Potassium Intercalation into Graphite - Daisuke IGARASHI; Kei KUBOTA; Tomooki HOSAKA; Ryoichi TATARA; Tsuyoshi INOSE; Yuji ITO; Hirofumi INOUE; Masataka TAKEUCHI; Shinichi KOMABA (Electrochemistry, 2021)
An effect of crystallinity of graphite on formation of graphite intercalation compounds (GICs) and reversibility in K cells was studied by comparing that in Li cells. Though high reversible capacities and coulombic efficiencies of graphite electrodes in K cells were achieved during initial cycles regardless of the crystallinity, high crystallinity graphite demonstrated less potential-hysteresis and superior capacity retention to low crystallinity graphite. Operando XRD measurement confirmed similar staging process of K-GICs for both graphite, however, high crystallinity graphite transformed into higher crystallinity of K-GIC as well as higher reversibility of potassium de-/intercalation than low crystallinity graphite. A turbostratic disorder in low crystallinity graphite led to redox-potential split and lower crystalline K-GIC and potassium-extracted graphite. Thus, the crystallinity of graphite, which includes coherence length and the degree of random stacking, is found to be a predominant factor for highly reversible potassium intercalation, which differs from the lithium case. We concluded that the high crystallinity is of importance for the application of graphite to long-life potassium-ion batteries.